2020
DOI: 10.3847/1538-4357/ab76d3
|View full text |Cite|
|
Sign up to set email alerts
|

Extreme Ultraviolet and Soft X-Ray Diffraction Efficiency of a Blazed Reflection Grating Fabricated by Thermally Activated Selective Topography Equilibration

Abstract: Future observatories utilizing reflection grating spectrometers for extreme ultraviolet (EUV) and soft x-ray (SXR) spectroscopy require high-fidelity gratings with both blazed groove facets and custom groove layouts that are often fanned or feature a slight curvature. While fabrication procedures centering on wet anisotropic etching in mono-crystalline silicon produce highly-efficient blazed gratings, the precision of a non-parallel groove layout is limited by the cubic structure of the silicon crystal. This m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Previous test campaigns have demonstrated that reflection gratings operated in an extreme off-plane mount can be measured for soft x-ray diffraction efficiency using a beamline facility suitable for short-wavelength reflectometry [2,6,24,25]. The experiments described here took place at beamline 6.3.2 of the ALS, which provides a highly-coherent beam of radiation tunable over extreme UV and soft x-ray wavelengths that strikes a stage-mounted optic [19][20][21].…”
Section: Beamline Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous test campaigns have demonstrated that reflection gratings operated in an extreme off-plane mount can be measured for soft x-ray diffraction efficiency using a beamline facility suitable for short-wavelength reflectometry [2,6,24,25]. The experiments described here took place at beamline 6.3.2 of the ALS, which provides a highly-coherent beam of radiation tunable over extreme UV and soft x-ray wavelengths that strikes a stage-mounted optic [19][20][21].…”
Section: Beamline Experimentsmentioning
confidence: 99%
“…This layer was sputter-coated on the replica in an identical fashion to Miles, et al [2]: 5 nm of chromium was deposited for adhesion followed immediately by 15 of gold, without breaking vacuum. Because this thickness is several times larger than the 1/e penetration depth in gold at grazing-incidence angles, it is justified to treat this top film as a thick slab in this context [6,26].…”
Section: Beamline Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cash, 1991;McEntaffer, 2019). Recently, using state-of-the-art production technology to produce master structures of high quality for the grating replication process, very promising performance was experimentally verified at prototype structures by Miles et al (2018) and by McCoy et al (2020) for the soft X-ray range. The measurements concerned photon energies from 200 eV up to 1200 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike at a synchrotron, in space science one finds the sources at infinity, and then as shown by Cash (1983) the removal of the principal aberration in the diffraction process can be achieved in the grating structure by linearly varying the groove separation along the beam footprint in so-called radial groove gratings. The latest study by McCoy et al (2020) considers the production of such radial groove gratings. Instead Miles et al (2018) concentrated on the use of wet anisotropic etching into monocrystalline silicon.…”
Section: Introductionmentioning
confidence: 99%